Inclusion policies and extension of compulsory school: Scope, debt and challenges in the realization of the right to education - Gluz, Nora; Oliveira, Dalila Andrade; Lima Rodrigues, Cibele Maria (Education Policy Analysis Archives, 2018)
This introductory text presents the axes that guide the dossier, Policies for Inclusion and Extension of School Obligations, organized by the Working Group on Educational Policies and the Right to Education of the Latin American Council of Social Sciences (CLACSO). Through research results, the articles show advances in the realization of the right to education, the contradictory dynamics assumed by the extension of rights in contexts of exclusion, and the persistence of inequalities. Covering the period from the crisis of the Washington consensus to the current restoration of rights in the world, the papers allow us to think about different meanings attributed to “school inclusion” in educational policies, the ambiguities resulting from their appropriation, and the attacks on the processes of democratization of education where neoliberal responses have presented new arguments in the public scene. The texts will be published in two editions, ensuring thematic diversity and a balance between general writings on policies and case studies.